On Nonlinear Generalized Caputo Fractional Implicit Volterra-Fredholm Model - Jameel, Saif Aldeen M.; Hamoud, Ahmed A. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we prove some new existence and uniqueness results of solutions for nonlinear fractional implicit integro-differential equations of Hadamard-Caputo type with fractional boundary conditions. The reasoning is inspired by diverse classical fixed point theory, such as the Schauder and Banach fixed point theorems. The theoretical findings are illustrated through an example.